2018
DOI: 10.22581/muet1982.1801.18
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of Different Water Table Depths on Water Use, Yield and Water Productivity of the Okra Crop

Abstract: An experimental study was carried out on a Lysimeter with the aim of partially meeting WRs (Water Requirements) of the Okra crop through SWT (Shallow Water Table) while maintaining the SWT at various levels below the ground surface. Under the study, CWR (Crop Water Requirement), yield, water productivity, salt accrual and contribution of SWTs towards meeting the CWR are assessed. The study was designed in accordance with the principles of CRD (Complete Randomized Design) with three treatments and four replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Crops grown at ≤ 1.00 WTDs do not need surface irrigation, as all of their water requirements can be met from the shallow water table. However, the water requirements of the crops cultivated at WTDs > 1.00 m are fulfilled from both sources, that is, surface irrigation and groundwater contribution (Gul et al, 2018; Kahlown et al, 2005). Hence, both facilities were arranged in this experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crops grown at ≤ 1.00 WTDs do not need surface irrigation, as all of their water requirements can be met from the shallow water table. However, the water requirements of the crops cultivated at WTDs > 1.00 m are fulfilled from both sources, that is, surface irrigation and groundwater contribution (Gul et al, 2018; Kahlown et al, 2005). Hence, both facilities were arranged in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…No work could have been carried out to determine the GW contribution towards meeting banana and papaya ET at different WTDs and soil types. However, Ashraf et al (2018) and Gul et al (2018) found that the GW contribution towards meeting the ET of the major crops decreased with the increase in WTD. The regression analysis shows a strong inverse correlation between GW contribution, WTDs and soil types (Figure 9).…”
Section: Groundwater (Gw) Contributionmentioning
confidence: 99%
“…Due to inappropriate drainage system in Sindh, this will raise water-table depths leading to water-logging and salinity. High water-table (≤ 1.50 m) is already prevailing in the Sindh province [25]. The situation will become worsen if the management practices shall not carry out.…”
Section: Climate Change -Trend Analysismentioning
confidence: 99%